Cover Image. Issue 3 (20th May 2021) - Hespel, Adrien‐Maxence; de Swarte, Marie; Anderson, Kimberly; Weiss, Richard; Hathcock, John
Abstract : Cover caption: The cover image is based on the Case Report Features of a rare peripheral primitive neuroectodermal tumour arising from the thoracic spine in a juvenile canine patient by Adrien‐Maxence Hespel et al., https://doi.org/10.1002/vms3.449 .